GURU DAN BUDAYA HIDUP SEHAT - Edwita Edwita (Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2006)
Health is actually a wealth for human life. Health quality is determined by one’s health condition and it will affect working productivity. The teacher’s healthy life, which can be built up continuously through living in his/her good and healthy environment, will also influence his/her teaching quality. The teacher is expected to become a model and motivate the students and the society to do a healthy life not only physically but also spiritually. To meet this expectation, the teacher should have a perfect healthy life.